Stingray (Neotrygon orientalis) population structure based on catch data in Nusantara Fishery Port (Pelabuhan Perikanan Nusantara/PPN) Brondong, Lamongan - Sukmawati, Mayang; Setiawan, Fajar; Maisaroh, Dian Sari (UIN Sunan Ampel Surabaya, 2022)
Stingray is a type of fish included in the Elasmobranchii class that has high economic potential. This study aims to determine the sex ratio, growth rate, length-weight relationship, condition factor, mortality and exploitation rate of stingray (Neotrygon orientalis) in PPN Brondong, Lamongan. Samples N. orientalis collected every week starting from October 1, 2019 until January 2021 and weighed in total body weight (gram) and measured in total body length (cm) then sex was identified based on macroscopic characteristics of gonads. The results showed that the sex ratio of N. orientalis was 1.4 : 1. Length growth value (K) of male and female N. orientalis are 0.0285 and 0.0233, respectively, which show a slow growth time to reach the asymptotic length (K≤ 0.5). Based on the analysis of the relationship between length and weight, the results show that b value are 1.9394 and 2.2023 in male and female N. orientalis, respectively, which means length growth rate faster than weight growth (b< 3, negative allometric). N. orientalis are included in the category of flat (thin) fish with condition factor values ranging from 0.2462-3.9227. The total, natural, and fishing mortality rate were 0.395, 0.177, and 0.218, respectively. The exploitation rate is 0.551 where the value has exceeded the optimum value 0.5, which means that N. orientalis landed at the PPN Brondong, Lamongan has indicated overfishing caused by excessive fishing activity.